DOI: 10.22215/etd/2017-12223
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter Wave Small Cell Network Planning for Outdoor Line-of-Sight Coverage

Abstract: The increasing spectrum demand drives next-generation wireless networks to use higher carrier frequencies. The millimeter wave band has orders of magnitude more bandwidth available and is considered as an important candidate for providing most of the capacity in a future heterogeneous network. Moreover, network densification is necessary for enhanced capacity and high-rate coverage. However, deploying a very large number of the base stations might be prohibitively costly. We develop an outdoor small cell milli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
(105 reference statements)
0
7
0
Order By: Relevance
“…A subset of the IAB nodes are assumed to be IAB donors (or gateways) and no gateway placement strategy is involved, which may result in overloading some IAB-donors or increasing the number of hops. In [63] the authors design a wireless backhaul network planner to reduce the cost of the deployment. The main objective of the algorithm was to maximize the overall coverage while minimize the number of gateways.…”
Section: B Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A subset of the IAB nodes are assumed to be IAB donors (or gateways) and no gateway placement strategy is involved, which may result in overloading some IAB-donors or increasing the number of hops. In [63] the authors design a wireless backhaul network planner to reduce the cost of the deployment. The main objective of the algorithm was to maximize the overall coverage while minimize the number of gateways.…”
Section: B Related Workmentioning
confidence: 99%
“…Unlike [62], [63], [64], [65], [66], which address GLP in a different way, our work aims to fill the research gap found in previous studies by proposing the K-GA heuristic for locating a given number of gateways such that the average number of hops from small cells to gateways is minimized and backhaul network capacity is maximized in an efficient way.…”
Section: B Related Workmentioning
confidence: 99%
“…This includes things like mobile health, selfdriving cars, manufacturing and entertainment, education, smart grids, big data analysis, smart cities and homes, aerospace, ocean exploration, emergency response, and mobile platforms, among others [1]. As can be verified from the literature, a base station (BS) can transmit data with up to a radius of approximately 200ms while using 5G mmWave technology [2]. So far, the experimental evidence suggests that deploying base stations (BSs) with a radius of at least 200 m can solve the coverage issue in outdoor areas by utilizing direct line-of-sight communication.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the experimental evidence suggests that deploying base stations (BSs) with a radius of at least 200 m can solve the coverage issue in outdoor areas by utilizing direct line-of-sight communication. However, it is important to note that opting for smaller radius values would mean needing a significantly larger number of base stations to ensure complete coverage for users [2,3]. In particular, note that any pair of BSs can be connected by using cables to form the backbone network structure.…”
Section: Introductionmentioning
confidence: 99%
“…There is little work on the GLP in UDNs (or UDCs). In [42] the authors explained dense base station deployment for assigning larger bandwidth resources to users. The main objective of the algorithm was to maximize the overall coverage while minimizing the number of gateways.…”
Section: Wired Solutionmentioning
confidence: 99%